Palatal Positioning of Implants in Severely Resorbed Posterior Maxillae - F. Atamni; M.Atamni; M.Atamna (Romanian Society of Oral Rehabilitation, 2011)
To evaluate an alternative treatment for rehabilitation of the severely resorbed posterior maxilla with palatal positioning of implants using the pre-existing anatomic features. Material and Methods: A retrospective study was conducted of thirty eight patients who received palatally positioned implants in the posterior maxilla using optimally the palatal curvature to avoid sinus grafting between Sep. 2005 and Sep. 2009. Patients with class IV and V atrophied maxillae according to the Cawood and Howell classification were included in this study. All patients received implant-retained fixed metal ceramic crowns. Panoramic radiographs and computerized tomographs of the maxillae had been made prior to surgery. Patients were followed-up for forty eight months after prosthesis delivery. Mesial and distal bone loss around the implants was measured on periapical radiographs and the largest value was considered as the bone loss. Periotest values (PV) of inserted implants were analyzed. Results: Thirty eight resorbed posterior maxillae were treated with fixed prosthesis supported by a combination of 196 upright and palatally positioned implants. All implants were placed as planned, 56 implants were placed in the palatal curvature through optimal use of the anatomic features of the posterior arch,140 implants were placed in upright position using the residual pristine bone. The success rate of palatally positioned implants during the four-years observation period was 96% (54/56). Clinical evaluation of the results showed stable implants according to PV. The mean bone loss of implants with palatal tilting at the 12 months evaluation of loading was 0.88±0.59, No complications were recorded and there was no infection or inflammation. Conclusion: Palatal positioning of implants in situation where there is sufficient palatal bone medial to the maxillary sinus, may be a predictable alternative to avoid sinus grafting for rehabilitation of the atrophied posterior maxilla.